IMPLEMENTATION OF LAKIP AS A PERFORMANCE EVALUATION TOOL AT THE REGIONAL SECRETARIAT OF NORTH ACEH REGENCY - Diva Nabilah; Putri Nadia; Durratun Nafisah; Riska Maulina; Intan Cahyani Rachman; Halimatus Sa'diyah; M. Yazid AR (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2023)
This study aims to evaluate the implementation of the Government Agency Performance Accountability Report (LAKIP) at the Regional Secretariat of North Aceh Regency, focusing on its effectiveness in achieving performance targets, identifying challenges, and assessing its relevance to strengthening accountability, transparency, and the quality of local governance. The study employs a descriptive qualitative approach, using in-depth interviews with government officials and document analysis, including strategic plans, performance reports, and relevant regulations. The collected data were analyzed thematically to identify patterns, supporting factors, and obstacles in the implementation of LAKIP. The findings indicate that the implementation of LAKIP in North Aceh Regency has been relatively effective in promoting accountability and achieving strategic performance indicators, particularly in governance and human resource development. However, challenges remain, including budget limitations, inter-agency coordination issues, and gaps in human resource capacity. To enhance LAKIP’s effectiveness, it is necessary to strengthen officials’ competencies, optimize budget management, and increase public participation in the performance evaluation process of local government.